The Role of Oxidative Stress and Inflammation in X-Link Adrenoleukodystrophy - Yu, Jiayu; Chen, Ting; Guo, Xin; Zafar, Mohammad Ishraq; Li, Huiqing; Wang, Zhihua; Zheng, Juan (Frontiers in Nutrition, 2022)
X-linked adrenoleukodystrophy (X-ALD) is an inherited disease caused by a mutation in the ABCD1 gene encoding a peroxisomal transmembrane protein. It is characterized by the accumulation of very long-chain fatty acids (VLCFA) in body fluid and tissues, leading to progressive demyelination and adrenal insufficiency. ALD has various phenotypes, among which the most common and severe is childhood cerebral adrenoleukodystrophy (CCALD). The pathophysiological mechanisms of ALD remain unclear, but some vitro/vivo researches showed VLCFA could induce oxidative stress and inflammation leading to damage. And the evidences that oxidative stress and inflammation are increased in patients with X-ALD also prove it is the potential mechanism of brain and adrenal damage. Therefore, normalizing the redox balance becomes a critical therapeutic target. This review focuses on the possible predictors for the severity and progression of X-ALD, the potential mechanisms of pathogenesis, and the promising targeted drugs involved oxidative stress and inflammation.